Strategi Pemasaran Usahatani Jamur Tiram Di Dusun Basseang Kec. Anreapi Kabupaten Polewali Mandar - Nurhaya Kusmiah; Mustajab Mustajab; Hasanuddin Kandatong (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
Oyster mushroom is a food plant with a hood that’s almost same as oyster shell, which currently great demand by consumers. This study aims to determine internal external factors of Oyster Mushroom Marketing Strategy in Basseang . The method used in this study is SWOT analysis to identify marketing strategic can be applied to farming with analyze of EFAS and IFAS tables and using SWOT diagrams to determine the position of farming. Based on the research the data showing that the strength factor can cover the existing weaknesses where the strength factor obtained a total value of 1.9 greater than the weakness factor with a total value of 1.23 this can indicate that strength can support the development of Oyster Mushrooms in Basseang. External factors have an opportunity factor with a total value of 1.56 greater than the threat factor with a total value of 1.44 this indicates that oyster mushrooms in the Basseang have a very large potential opportunity . Meanwhile, based on the SWOT diagram, the position of the oyster mushroom farming is in Quadrant I, namely aggressive criteria, where the business position is very safe, with this position the farm needs to increase production and increase promotion.